Flexural Strength Of Wall Panels With Wiremesh Reinforcement - Maharani, Nabella, Muhammad Ujianto, ST., MT, Yenny Nurchasanah, S.T., M.T (2016)
Wall is one of the important elements of the building and serves to separate and form a space in residential buildings or storied. After brick and lighweight cooncrete walls to the cur rent development of construction projects have come the use of wall panels. Wall panels are generally made using a concrete mixture like usual (water, fine aggregates, coarse aggregates, cement) and given reinforcement inside. Reinforcement used in this re search is wiremesh. The aims of this research are to analizing the value of compressive strength of concrete cylinder, analyzing value of compressive strength of concrete cylinder, to analyzing flexural strength of wall panels without wiremesh reinforceme nt, and to analyzing value flexural strength of wallpanels with wiremesh reinforcement The specimen is made with dimension width 50 cm, length 100 cm, and a height of 7 cm for flexural strength testing. Life of concrete that is planned is 28 days. The purp ose of this research is to analyze the flexural strength of wall panels with wiremesh reinforcement. In this research there are several stages. The first step is preparation of equipment and materials. The second stage includes the examination of materials , mix design and manufacture of concrete mix. The third stage is the manufacture and maintenance of the test specimen. The fourth stage is testing of compressive strength concrete and flexural strength wall panels. The fifth stage is the data analysis, dis cussion, and conclusion. Results of lightweight concrete compressive strength is 21, 18 MPa, flexural strength panel walls without reinforcement wiremesh is 3.293 MPa, flexural strength while the wall panels with wiremesh reinforcement is 5.694 MPa.